When Debt Never Matures: A Phenomenological Study of the Belis Tradition in Sikka Krowe - Anggraini Winata, Delicia Devi; Tjaraka, Heru (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to explore the meaning of obligations and assets in the belis tradition of Sikka Krowe customary marriage from a financial accounting perspective. Belis is a cultural practice the embodies social and symbolic values while also involving economic value, raising issues related to recognition, measurement, and reporting under Indonesia Financial Accounting Standars (PSAK). This research employs a qualitative approach using transcendental phenomenology. Data were collected through in-depth interviews with four informants, including a customary leader, a married couple, and a newlywed, all of whom have direct experience with the belis tradition. The findings reveal that belis obligations are perceived as enduring customary responsibilities that extend across generations and lack a definite settlement period, making them inconsistent with the PSAK concept of liabilities. Consequently, belis debt cannot be recognized as a formal liability in financial statements. Moreover, belis assets are not intended to generate economic benefits but function as symbols of honor and mechanisms for strengthening kinship ties. Study highlights the gap between PSAK based accounting and culturally rooted practices and proposes qualitative and narrative disclosure of belis obligations in the CALK as ongoing socio cultural obligations.